Asymmetry and Aggregation in the EU - Mayes, D. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
This book presents a clear exposition of what constitutes asymmetry in economics. It provides an empirical application of these ideas in the case of the EU. In particular, it shows how important asymmetry is for the appropriate design of policy in the Euro Area.